حساب الناقلية ومعامل العازلية الكهربائيين لبلازما فيرمي الواقعة تحت تأثير حقل مغنطيسي خارجي (Latakia University Journal -Basic Sciences Series, 2017)
تم في هذا البحث حل المعادلة الحركية شبه الكمومية لـلانداو- سيلين عند استخدام التأثير المتبادل بين أشباه الجسيمات في بلازما فيرمي الواقعة تحت تأثير حقل مغنطيسي خارجي، ومن ثم الحصول على نتائج أكثر دقة لبعض الخواص كالناقلية ومعامل العازلية، نظراً لأهميتهما في دراسة خواص البلازما بتابعية بارامترات لانداو ، وبعدئذ تمت مقارنة النتائج التي تم الحصول عليها مع نتائج طرق أخرى لتعيين هذين المعاملين.Landau,s – Silin Semi Kinetic Equation has been solved by this scientific paper. After taking into consideration the mutual effect between quasi particles in Fermi's Plasma under a magnetic field to get more accurate results related to coming up with some characteristics of this sphere. Like the conductivity and dielectric coefficient due to their necessity in the plasma's characteristic study depending on Landau's parameters ( ) and comparing them to the results of other ways for these parameters to be calculated.